Experimental study on heat transfer enhancement in solar air heater by electric field - T. Kiatsiriroat (2018)
An experimental study on the thermal performance of a solar air heater under an electric field has been completed. The solar air heater is a flat-plate type with the dimensions of 1.2 m × 1.8 m and an air channel at the back of the solar absorbing plate. The unit is facing south and inclines 18ofrom the horizontal plane. Nine electrodes, each 0.5 mm in diameter, have been installed in the air channel and set across the air flow direction. The effects of the electrode spacing and the air Reynolds number on the heat rate obtained by the collector are experimentally studied. From the experiments and under steady-state condition, with the solar radiation between 840-1100 W/m2, it was found that the electric field could enhance the heat rate from the collector significantly at a low Reynolds number. At a Reynolds number of 200, the heat rate could be 1.8 times that without electric field while the power supply of the electric field is only 0.5-0.6 W with the voltage of 10 kV. A higher voltage results in a higher heat transfer enhancement, but there is a limit of the breakdown voltage. In this work, a model has been developed to predict the heat transfer data, and the predicted results agree very well with the experimental results.© Taylor and Francis Group, LLC.